Towards an architecture of inclusivity : the building edge as the articulated urban connector, encouraging multiplicity and restructuring power relations - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2023)
Mini Dissertation (MArch (Prof))--Univewrsity of Pretoria, 2022.